Maternal diet and gestational diabetes mellitus modestly influence children's growth during their first 24 months - Saros, Lotta; Vahlberg, Tero; Koivuniemi, Ella; Houttu, Noora; Tertti, Kristiina; Shivappa, Nitin; Hébert, James R.; Niinikoski, Harri; Laitinen, Kirsi (Wiley, 2026)
Objective
To evaluate whether diet and gestational diabetes mellitus (GDM) during pregnancy influence children's growth during their first 24 months.
Methods
Growth data of children (n = 378) of women with overweight/obesity were obtained from clinic records (birth, 3, 6, 12 and 24 months), and variables (standard deviation scores (SDS) or percentages) were calculated based on Finnish growth charts. Body composition was measured by air displacement plethysmography (n = 73, 24 months). Diet was assessed (diet quality index, nutrient intakes and diet inflammatory index (DII®)) in early and late pregnancy. GDM was determined by an oral glucose tolerance test.
Results
A good dietary quality in early pregnancy associated positively with the children's height at each time point (adj. mean difference range = 0.28–0.30 SDS, p < 0.05) and head circumference at 12 and 24 months (adj. mean difference range = 0.38–0.42 SDS, p < 0.05). A good dietary quality in late pregnancy associated with a lower fat mass in children (adj. mean difference = −0.69, p < 0.05). A higher DII was correlated with a higher weight at 24 months but a reduced height at each time point (adj. p < 0.05). GDM associated negatively with the children's head circumference at birth and 6 months (adj. mean difference range = −0.43 to [−0.22] SDS, p < 0.05).
Conclusions
Consuming a good quality diet during pregnancy associated with a greater infantile height and head circumference but a lower adiposity in 2-year-old children. GDM may lead to a slightly smaller head circumference in early infancy. Mothers with overweight or obesity could support their children's growth by consuming a good quality diet, with low inflammatory potential during pregnancy.